2014
DOI: 10.1159/000362633
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroprotective Effect and Probable Mechanism of <smlcap>DL</smlcap>-3-n-Butylphthalide in Brain Diseases

Abstract: 3-n-Butylphthalide (NBP), one of the chemical constituents of celery oil, is used for the treatment of many central nervous system diseases, including Parkinson's disease, Alzheimer's disease and cerebral ischemia. NBP showed potent neuroprotective effects by decreasing oxidative damage, inhibiting inflammatory responses, improving mitochondrial function, and reducing neuronal apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Butyphthalide, a novel drug independently developed by China, has been extensively applied in the treatment of nervous system diseases such as ischemic cerebrovascular disease and dementia. Butyphthalide may protect nerves through inhibiting cell apoptosis by reducing caspase enzymes activation, inhibiting release of cytochrome-c and down-regulating Fas protein expression, protecting damaged neurons by restraining inflammatory reactions, inhibiting delayed neuronal death by eliminating free radicals, relieving neuron damages by inhibiting calcium overloading, alleviating neurotoxicity by reducing release of excitatory amino acid, controlling encephaledema by protecting blood brain barrier and improving microcirculation of cerebral ischemia area and energy metabolism of brain cells 15-19. Animal pharmacodynamics study suggested that butyphthalide could block multiple pathological links of cerebral injury induced by ischemic cerebral stroke, narrow infarction area of local cerebral ischemia of rats, relieve encephaledema, improve cerebral energy metabolism and microcirculation and blood flow in cerebral ischemic region, inhibit apoptosis of nerve cells, and resist cerebral thrombosis and anti-platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Butyphthalide, a novel drug independently developed by China, has been extensively applied in the treatment of nervous system diseases such as ischemic cerebrovascular disease and dementia. Butyphthalide may protect nerves through inhibiting cell apoptosis by reducing caspase enzymes activation, inhibiting release of cytochrome-c and down-regulating Fas protein expression, protecting damaged neurons by restraining inflammatory reactions, inhibiting delayed neuronal death by eliminating free radicals, relieving neuron damages by inhibiting calcium overloading, alleviating neurotoxicity by reducing release of excitatory amino acid, controlling encephaledema by protecting blood brain barrier and improving microcirculation of cerebral ischemia area and energy metabolism of brain cells 15-19. Animal pharmacodynamics study suggested that butyphthalide could block multiple pathological links of cerebral injury induced by ischemic cerebral stroke, narrow infarction area of local cerebral ischemia of rats, relieve encephaledema, improve cerebral energy metabolism and microcirculation and blood flow in cerebral ischemic region, inhibit apoptosis of nerve cells, and resist cerebral thrombosis and anti-platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%